Subcutaneous checkpoint inhibition is equivalent to systemic delivery when combined with nelitolimod delivered via pressure-enabled drug delivery for depletion of intrahepatic myeloid-derived suppressor cells and control of liver metastases - Diwakar Davar; Yujia Liu; Jason Laporte; Prajna Guha; Steven C Katz; Chandra C Ghosh; Lauren Cournoyer; Alizee Ballarin; Ilan B Layman; Molly Morrissey; Kayla Fraser; Shriya Perati; et al. (Journal for ImmunoTherapy of Cancer)
Background Toll-like receptor 9 (TLR9) agonists induce inflammatory responses that promote the killing of infectious micro-organisms, cancer cells and develop adaptive immune responses. Their ability as immunomodulators to enhance the activity of checkpoint inhibitors (CPI) in treating liver tumors is limited in part by the distinctive biology of intrahepatic myeloid-derived suppressor cells (MDSC) and challenges with tumor-specific therapeutic delivery. We have shown that the regional delivery of type C TLR9 agonist via pressure-enabled drug delivery (PEDD) system improves delivery to the tumor, enhances depletion of MDSCs and overall, stimulates the immune system in combination with or without CPI. Currently, CPIs are delivered intravenously, although there is a growing interest in its subcutaneous (SQ) administration. We compared nelitolimod formerly known as SD-101 administered using PEDD in combination with systemic (Sys) or SQ CPI in murine liver metastases (LM).Methods The LM model was developed by injecting MC38-Luc cells via the spleen of 8–12 week old male C57/BL6 mice followed by splenectomy. After a week, fluorescently labeled nelitolimod (10 µg/mouse) was delivered via PEDD and co-administered anti-programmed cell death-1 (α-PD-1) either via Sys or SQ. Tumor burden was monitored by in vivo imaging system. Serum cytokine levels were analyzed by Luminex. Tissues were harvested on Day 3 (D3) or Day 10 (D10) post-PEDD to enrich CD45+ cells and were analyzed via NanoString targeted transcriptomics (D3) or flow cytometry (FC, D10) to interrogate immune cell populations (D10). For NanoString analysis, the innate immune panels were selected, and for FC, MDSCs (CD11b+Gr1+), B cells (B220+), dendritic cells (DC, CD11c+), T (CD3+) cells, and M1-like macrophages (F4/80+CD38+Egr2−) were quantified.Results Nelitolimod delivered via PEDD resulted in changes in innate and adaptive immune cells within LM, including depletion of liver MDSC and increased M1-like macrophages in the liver, which are supportive of antitumor immunity. While CPI monotherapy failed to control tumor progression, nelitolimod and CPI combination improved LM control, survival and antitumor immunity beyond the nelitolimod monotherapy effect, irrespective of CPI delivery route.Conclusion The SQ route of CPI delivery was equivalent to Sys in combination with nelitolimod, suggesting SQ-CPI may be a rational choice in combination with PEDD of nelitolimod for liver tumor treatment.